Upaya Meningkatkan Kemampuan Berpikir Kritis Mahasiswa Melalui Pembelajaran Discovery Learning Berbasis Assessment Learning - Eric Dwi Putra; Ria Amalia (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
Improved learning will continue to be done to continuously improve the quality of learning. One of the efforts made through discovery learning is based on assessment learning. Collaborating between discovery learning and assessment learning is expected to improve students' critical thinking skills in discrete mathematics courses. Classroom action research conducted in 2 cycles where each cycle carried out as many as 4 (four) meetings. The results showed that a) Implementation of discovery learning based on assessment learning that can improve students' critical thinking skills is carried out in 7 stages, namely stimulation, problem statement, data collection, data processing, verification, generalitation and peer assessment. The seven stages work together to create independent learning and train students' thinking skills. b) Students' critical thinking skills have increased by 33.33%. This percentage indicates that discovery learning based on assessment learning can improve students' critical thinking skills